Peran Tokoh Masyarakat dalam Upaya Menjaga Kerukunan Umat Beragama di Komplek Astra Blok 1 Jalan Tuar Medan Amplas - Lubis, Haidir; Khatani, Aaliya Ainina; Punto, Afanin Gladis Dwi; Putri, Amanda; Dalimunthe, Cindy Chairunnisa; Aidah, Hasnil; Irawan, Hayyatu Syifa; Ayundira, Miranda; Ar Ridho Tanjung , Muhammad Siddiq (UNIVERSITAS SERAMBI MEKKAH, 2025)
This research aims to examine the role of community leaders in maintaining religious harmony in the Astra Block 1 Complex, Medan Amplas. The lack of social interaction due to the individualistic modern lifestyle is a major challenge in creating harmony among residents with diverse social, economic and cultural backgrounds. The method used is descriptive qualitative research, with interviews of two community leaders as the main data source. The research results show that community leaders function as unifiers and facilitators, able to direct social and religious activities that encourage harmony. They show an attitude of tolerance and active involvement in interfaith activities, thereby reducing the potential for conflict. Good communication and inclusive leadership from community leaders play an important role in building mutual respect between residents. It is hoped that this research can provide input for the development of programs that support harmony and cooperation in society. By increasing awareness of the importance of social interaction, community leaders are expected to be able to create a harmonious and conducive environment for all citizens.